Struktur dan Sifat Piroklor Oksida BixY2-xTi2O7 - Ismunandar Ismunandar; Brendan J. Kennedy (Institut Teknologi Bandung, 2002)
Structure and bonding properties of some quarternary pyrochlore oxides, BixY2-xTi2O7, 0.2 £ x £1.63, have been determined by analysis of powder neutron and synchrotron X-ray diffraction data. These oxides form a series of cubic pyrochlore type of oxides, where the cell size increases with Bi content. The expansion of the cell size is accompanied by decreasing of the electron densities of Bi cations and significant shift of Bi-O charge transfer. The refinements indicated that at high Bi contents, the Bi/Y and O sites are not fully occupied. This results indicates that the smaller Ti2O6 network in titanate pyrochlores can not fully accommodate the large Bi cations. There is no indications of any pyrochlore formation from the reaction of (Bi2O3:2TiO2). Temperature dependent studies on this compositions revealed that neither phase transitions nor pyrochlore phase were observed in the temperature range 25 £ T £1100°C.